Non-Coding RNAs: New Dawn for Diabetes Mellitus Induced Erectile Dysfunction - Xu, Wenchao; Jiang, Hongyang; Liu, Jihong; Li, Hao (Frontiers in Molecular Biosciences, 2022)
Erectile dysfunction (ED) is a common sexual dysfunction in males, with multifactorial alterations which consist of psychological and organic. Diabetes mellitus (DM) induced erectile dysfunction (DMED) is a disconcerting and critical complication of DM, and remarkably different from non-diabetic ED. The response rate of phosphodiesterase type 5 inhibitor (PDE5i), a milestone for ED therapy, is far from satisfactory in DMED. Unfortunately, the contributing mechanisms of DMED remains vague. Hence, It is urgent to seek for novel prospective biomarkers or targets of DMED. Numerous studies have proved that non-coding RNAs (ncRNAs) play essential roles in the pathogenesis process of DM, which comprise of long non-coding RNAs (lncRNAs) and small non-coding RNAs (sncRNAs) like microRNAs (miRNAs), PIWI-interacting RNAs (piRNAs) and circular RNAs (circRNAs). However, the implications of ncRNAs in DMED are still understudied. This review highlights the pathophysiology of DMED, summarizes identified mechanisms of ncRNAs associated with DMED and covers the topic of perspectives for ncRNAs in DMED.